Lack of "ventricular interdependence" in constrictive pericarditis and atrial septal defect - Maulik Kalyani; Bhavik Champaneri; Shyam S Kothari (Wolters Kluwer Medknow Publications, 2023)
Ventricular interdependence, i.e., reciprocal variations in the left and right ventricle pressures with respiration, is a hallmark of the hemodynamic diagnosis of constrictive pericarditis (CP). Similarly, respiratory variations in the mitral and tricuspid valve Doppler inflow velocities on echocardiogram are very helpful in the diagnosis of CP. We document the absence of such variations in a patient with CP and associated atrial septal defect. It is important to be mindful of this intuitively obvious fact; otherwise, the diagnosis of CP might be missed.